2018
DOI: 10.1088/1748-9326/aaa7bd
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impacts of slope aspect on forest dynamic succession in Northwest China based on FAREAST model

Abstract: Mountain forests provide the main water resources and lumber for Northwest China. The understanding of the differences in forests growing among individual slope aspects in mountainous regions is of great significance to the wise management and planning of these natural systems. The aim of this study was to investigate the impacts of slope aspect on forest dynamic succession in Northwest China by using the dynamic forest succession model (FAREAST).First, the simulated forest composition and vertical forest zona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…The knowledge on the influence of different slopes on the growth of understory seedlings is of great significance to successful forest management and planning (Hu et al, 2018). Higher solar radiation and relatively warmer and drier climate on the south-facing slopes may cause reduced tree growth and drought stress (Holland and Steyn, 1975;Måren et al, 2015)both of which are important controls on the growth behaviour, species composition and structure of its vegetation cover.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The knowledge on the influence of different slopes on the growth of understory seedlings is of great significance to successful forest management and planning (Hu et al, 2018). Higher solar radiation and relatively warmer and drier climate on the south-facing slopes may cause reduced tree growth and drought stress (Holland and Steyn, 1975;Måren et al, 2015)both of which are important controls on the growth behaviour, species composition and structure of its vegetation cover.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, soil properties did not vary between slope aspects, expect for potassium (highest in south-facing slopes. Hu et al (2018) examined the impacts of slope aspect on forest succession, and they found that the northern aspect provided higher height growth and biomass due to wetter climate and more soil moisture on the northern slopes. In a similar study, Sternberg and Shoshany (2001) monitored the influence of slope aspect on productivity in semiarid and arid sites in Israel, and concluded that the northern aspect presented higher productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Habitat-associated microclimate is also found to have a relationship with elevation (Clinton, 2003;Bell et al, 2014;Sunday et al, 2014). A single environmental factor is not always sufficient to explain local vegetation penology (Hwang et al, 2011) and it is probable that elevation, slope, and aspect in combination can have influence on tree structure and growth (Turner et al, 2001;Montoya-Pfeiffer et al, 2016;Hu et al, 2018), and increase the effects of IBE contributing to the geographic patterns of climatically and ecologically structured genetic variation.…”
Section: Ecological Factors Played the Most Prominent Roles In Drivinmentioning
confidence: 99%
“…Vegetation growth is mainly controlled by temperature, water, and sunlight duration [ 33 , 34 , 35 ]. In the high mountainous area, landform factors, e.g., elevation, slope, and aspect, often have significant impacts on microclimate conditions for vegetation.…”
Section: Methodsmentioning
confidence: 99%